Interrogative Slifting: More syntactic, less parenthetical - Arthur Stepanov; Penka Stateva (Glossa, 2016)
In this article we re-assess the recent analysis of interrogative Slifting (e.g., Who is a Martian, do you think?) proposed in Haddican et al. (2014). In this analysis, the two component clauses have an indirect syntactic relation to each other, and the semantic and pragmatic relationship between the “slift” question and the main clause is conceived around the notion of evidentiality. We advance an alternative proposal whereby interrogative Slifting can be construed more on a par with wh-scope marking questions attested in languages like German or Hindi. Placing interrogative Slifting alongside wh-scope marking, a more familiar and better-studied construction type, avoids certain empirical difficulties of the original analysis and paves a way toward a uniform treatment of its syntactic, semantic and interface properties.